KEBERHASILAN PENERAPAN BUDIDAYA PADI RAMAH LINGKUNGAN PADA PROGRAM GERBANG PANGAN SERASI DI KABUPATEN TABANAN - Rahayu, I Gede Urif Bayu Rahayu Urif Bayu; Sutjipta, I Nyoman; Oka Suardi, I Dewa Putu (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2019)
The level of food needs in agriculture sector is increasing. The condition urged the change on agriculture system. Therefore, anagriculture system that is more modern and more eco-friendly should be developed. The purpose of this study was to analyze the influence of the instructor competence on farmers’ behavior, the influence of innovation on farmers’ behavior, and the influence of the farmers’ behavior on the GPS program success. The study took place in Subak Timpag, Subak Koto Bongan, Subak Demung, and Subak Sungi I, which werepurposively selected. The research population was the members of the four subaks that apply eco-friendly paddy cultivation. The samples gathering in each of the subakwas done with Accidental Sampling technique with the total amount of 58 farmers. This study used Partial Least Square analysis. The study results showed that the instructor competence affected in actual way on the farmers’ behavior in the application of eco-friendly paddy cultivation; innovation affected in actual way on the farmers’ behavior in applying the eco-friendly paddy cultivation; and the farmers’ behavior affected in actual way on the success of the application of eco-friendly paddy cultivation. Keywords: GPS program, the application of eco-friendly paddy, the instructor competence, innovation, farmers’ behavior, and the program success.